Interstitial Lung Disease Related to Dematomyositis: Rare Case - Dian Megawati; Fanny Fachrucha (Malang Respiratory Journal, 2026)
Background: Dermatomyositis is a rare disease caused by inflammation of the muscles and connective tissues. One of the most common complications is interstitial lung disease (ILD) caused by a humoral immune response. Case: The case presented is a 48-year-old woman with classic symptoms of DM accompanied by respiratory symptoms and low lung fuctiond who was objectively proven to have ILD as a complication. Multidisciplinary collaboration was carried out to treat the patient. Conclusion: ILD is one of the complication and predictors of poor prognosis in DM patients. Comprehensive management and regular monitoring are needed to inhibit disease progression. Keywords: dermatomyositis, complication, ILD